The effect of hydrogen bonding on the reactivity of OH radicals with prenol and isoprenol: a shock tube and multi-structural torsional variational transition state theory study. Issue 20 (17th May 2022) - Mohamed, Samah Y.; Monge-Palacios, M.; Giri, Binod R.; Khaled, Fethi; Liu, Dapeng; Farooq, Aamir; Sarathy, S. Mani
Abstract : The reaction between prenol and isoprenol and the OH radical can proceed via OH addition to the double bond or by hydrogen abstraction. The branching ratios are governed by the intermolecular interactions between the reactants and multi-structural torsional anharmonicity. Abstract : The presence of two functional groups (OH and double bond) in C5 methyl-substituted enols ( i.e., isopentenols), such as 3-methyl-2-buten-1-ol (prenol) and 3-methyl-3-buten-1-ol (isoprenol), makes them excellent biofuel candidates as fuel additives. As OH radicals are abundant in both combustion and atmospheric environments, OH-initiated oxidation of these isopentenols over wide ranges of temperatures and pressures needs to be investigated. In alkenes, OH addition to the double bond is prominent at low temperatures ( i.e., below ∼700 K), and H-atom abstraction dominates at higher temperatures. However, we find that the OH-initiated oxidation of prenol and isoprenol displays a larger role for OH addition at higher temperatures. In this work, the reaction kinetics of prenol and isoprenol with OH radicals was investigated over the temperature range of 900–1290 K and pressure of 1–5 atm by utilizing a shock tube and OH laser diagnostic. To rationalize these chemical systems, variational transition state theory calculations with multi-structural torsional anharmonicity and small curvature tunneling corrections were run using a potential energy surface characterized at the UCCSD(T)/jun-cc-pVQZ//M06-2X/6-311++G(2df, 2pd) level of theory. A good agreement was observed between the experiment and theory, with both predicting a non-Arrhenius behavior and negligible pressure effects. OH additions to the double bond of prenol and isoprenol were found to be important, with at least 50% contribution to the total rate constants even at temperatures as high as 700 and 2000 K, respectively. This behavior was attributed to the stabilizing effect induced by hydrogen bonding between the reacting OH radical and the OH functional group of isopentenols at the saddle points. These stabilizing intermolecular interactions help mitigate the entropic effects that hinder association reactions as temperature increases, thus extending the prominent role of addition pathways to high temperatures. The site-specific rate constants were also found to be slower than their analogous reactions of OH + n -alkenes.